2020
DOI: 10.1371/journal.pone.0228558
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of delay in care seeking for diarrheal diseases among mothers/caregivers with under-five children in public health facilities of Arba Minch town, southern Ethiopia; 2019

Abstract: Background Timely and appropriate health care seeking for diarrhea of under-five children is important to reduce severe and life-threatening complications. However, different findings indicate that mothers of under-five children often delay in seeking care which in turn contributes to the death of large number of children without ever reaching a health facility. Therefore, a proper pinpointing of determinants of delay in seeking care informs intervention strategies for health service planners. Objectives Of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
8
19
0
Order By: Relevance
“…More importantly, our study indicated that caregivers with zero monthly income up to 20000 frs CFA were significantly associated with inappropriate health-seeking behavior. This is in accordance with the previous studies in Ethiopia [28,21,29]. Therefore, the present data indicate that poverty might be is an important hurdle on a family's decision about how to treat children's illnesses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More importantly, our study indicated that caregivers with zero monthly income up to 20000 frs CFA were significantly associated with inappropriate health-seeking behavior. This is in accordance with the previous studies in Ethiopia [28,21,29]. Therefore, the present data indicate that poverty might be is an important hurdle on a family's decision about how to treat children's illnesses.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are similar to that of [30]. However, this finding is contrary to study conducted in different parts of Ethiopia [27][28][29][30] where gender was not statistically significant to prompt health-seeking behavior. This might have been due to sociodemographic and cultural differences.…”
Section: Discussionsupporting
confidence: 69%
“…Educated mothers are more likely to have adequate knowledge on the importance of good hygiene as compared to uneducated mothers. This position is supported by Fikire et al in their study on understanding the determinants of delay in care-seeking for diarrhoea diseases among mothers/caregivers with U5C in public health facilities in Southern Ethiopia [ 47 ].…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that fever is the most frequent reason for caretakers seeking treatment for their under-five children [52]. Diarrhoea is not fatal itself, the delay and inappropriately healthcare utilisation leads to a high degree of mismanagement and resultant severe and life-threatening complications [53]. The low-cost and highly effective solution to reduce child mortality from diarrhoea is ORS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These low levels highlight the urgent need to educate caregivers on appropriate treatment [9]. In Africa, healthcare utilisation for diarrhoea in children is still low and considerable efforts are required to educate parents about diarrhoea and its prevention and proper treatment [53].…”
Section: Discussionmentioning
confidence: 99%